Caribou GPS Location Data - DeMars, Craig A.; Boutin, Stan (Dryad Digital Repository, 2017)
csv file containing GPS location data of boreal caribou. Note that data has been cleaned as per the methods outlined in the Journal of Animal ecology paper.